Manusia dan Kebebasan dalam Pandangan Taqi Misbah Yazdi: Studi Kritis Terhadap Jean Paul Sartre - Firmansyah, Beta; Triandi, Dikdik; Hamdani, Basrir; Fahmi, Zulkifli Reza (Jurusan Aqidah dan Filsafat Islam Fakultas Ushuluddin dan Adab UIN Sultan Maulana Hasanuddin Banten, 2023)
This research explores the views of Taqi Misbah Yazdi in criticizing the theory of human freedom according to Jean Paul Sarte. The discourse of human freedom has indeed been widely discussed, especially in modern times, especially in philosophy. Even in the West, this freedom is central to the discussion. The emergence of existentialism proves that the question of freedom has become a polemic among existentialist philosophers such as Soren Kierkegaard, Martin Haidegger, Karl Jasper and others. Researchers will focus on discussing Sartre's existentialism about human freedom. The method for this research is qualitative because this research is descriptive in nature and tends to use analysis. Process and meaning (subject perspective) are emphasized in qualitative research. The theoretical base is used as a guide so that the research focus is in line with the facts in the field. In this research, in terms of the existence of values, all the freedom that Sartre does certainly has weaknesses, namely it leads to anxiety, whereas in essence Sartre's freedom begins with human awareness of